Regional Planning for Reducing Disparities in Decentralized Development Systems: Perencanaan Regional untuk Mengurangi Kesenjangan dalam Sistem Pembangunan yang Terdesentralisasi - Abbas, Laith Zaid; kadhim, Ahmed Abbas (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Regional planning plays a crucial role in achieving balanced development by optimizing the use of natural and human resources across geographic areas. Specific Background: In federal systems like Iraq, the effectiveness of decentralized development plans is often undermined by ambiguity in administrative authority and the uneven distribution of wealth and resources among regions. Knowledge Gap: Limited research has examined how decentralization impacts the successful implementation of regional development plans in governorates not affiliated with any specific region. Aims: This study aims to analyze the role of decentralized regional planning in reducing disparities and improving the efficiency of development strategies in Iraq. Results: Using a SWOT analysis framework, the study reveals that administrative ambiguity and regional inequality are significant barriers to effective development. It highlights that empowering local authorities and redirecting investments toward marginalized areas can reduce unemployment, improve living standards, and stabilize populations. Novelty: The study uniquely links regional planning with decentralization and proposes a model integrating community participation and legislative restructuring as tools for sustainable regional development. Implications: The findings emphasize the urgent need for strategic regional planning that supports decentralized governance to achieve social and economic balance across Iraq’s diverse regions. Highlights: Decentralization improves efficiency and local development planning. Regional inequality weakens national development strategies. Public participation strengthens planning and implementation success. Keywords: Regional Planning, Decentralization, Development Policy, SWOT Analysis, Iraq